Analisis Perubahan Luasan dan Kerapatan Mangrove Menggunakan Data Citra Satelit Spot di Pesisir Teluk Pandan Kabupaten Pesawaran Provinsi Lampung - Andy Irawan; Isnaini Isnaini; Andi Agussalim (Jurnal Penelitian Sains, 2019)
Monitoring of mangrove forests periodically is important  to know the change of area coverage and the mangroves condition in the Teluk Pandan coastal of  Pesawaran District of Lampung Province. This research aims  to analyze changes of mangrove area and density in 2010 – 2015, to analyze the mangroves condition  also the correlation between mangrove density from the satellite image with the mangroves density  from the field and its accuration level in mangrove of Teluk Pandan coastal. This research was conducted in September 2015 – March 2016 using satellite image SPOT 4 in 2010 and SPOT 6 in 2015. This research used supervised method with a ground check  that has high accuration. The results showed that there was an increasing of mangroves density and also mangrove area coverage around 9 ha. The condition of mangroves in the coastal of Teluk Pandan categorized as good condition and Rhizophora apiculata was the dominant species with the highest IVI (Important Value Index). The correlation between NDVI (Normalized Difference Vegetation Index) values with the density of mangroves in the field has a high relationship with a R2 value of 0.9177. The accuration level of the image classification was 88.88% indicated  the good  accuracion level of the spatial distribution of mangroves.